Sprint characteristics of talent-selected female gymnasts age 9-11 years - Sand, W. A.; McNeal, J. R.; Borms, J.; Jemni, M. (2003)
Sprinting is a common power-oriented test used to assess physical abilities of athletes and children. Sprint ability of highly trained female child athletes has not been studied beyond total time to complete a given distance. The purpose of this study was to descriptively characterize the sprint abilities of talent-selected female gymnasts age 9 to 11 yr by assessing sub-intervals and total time of a 20 m dash. In conjunction with two testing sessions held by USA Gymnastics, infrared interval timers were placed at 3.33 meter intervals along a 20 m carpeted sprint area. The timing data were collected and analyzed via a custom electronic and computer interface. Athletes (N=225) began from a standing start and sprinted maximally. Interval times were measured and speeds were calculated. Data were analyzed collectively and by age group. Results (ANOVA age x interval, repeated measures on interval) showed that sprint characteristics (interval speeds) differed by time interval, age, and the age by interval interaction (all P<.05). Further analyses (ANCOVA, age x interval, BMI covariate, repeated measures on interval) indicated that age and size played large roles in the differences in sprint speeds observed, and the interval speeds main effect ceased to be statistically significant. These results indicated that the dominant differences in sprint ability for these athletes were due to size and age rather than a characteristic defined by the sprint intervals. Modest correlations were observed between height, mass, and interval times and interval speeds. The results indicate that there is a link between age, size, and sprint ability among these highly trained athletes. Future research should investigate the role of size and age on sprint ability in other athlete groups and the TOPs program may need to consider allometric scaling.